1524 Design and Implementation Of ICE-COVID, A Double-Blind Randomised Placebo-Controlled Trial on The Efficacy of Iota-Carrageenan Nasal and Throat Spray for Covid-19 Prophylaxis. (12th October 2021) - Lim, J Y; Jessop, Z M; Gibson, J A G; Jovic, T H; Combellack, E; Dobbs, T D; Healy, B; Humphreys, Ian R; Eccles, Ronald; Hutchings, Hayley A; Whitaker, Iain S
Abstract: Introduction: The severity of Covid-19 infection is associated with viral load. For infection to occur, viruses including SARS-CoV-2 must first penetrate the respiratory mucus to attach to the host cell surface receptors. Iota-carrageenan (I-C), a sulphated polysaccharide extracted from red edible seaweed, has shown efficacy against a range of viruses in clinical trials, through prevention of viral entry into respiratory host cells and in-vitro activity against SARS-CoV-2. Our aim, as an academic surgical department, was to design and implement a clinical trial to investigate whether I-C nasal and throat sprays are effective in reducing the rate and severity of Covid-19 infection. Method: The study is a single centre, double-blinded randomised controlled trial. Recruitment of 480 participants aged ≥18 years without previous Covid-19 infection and who have not yet been vaccinated, commenced in December 2020. Participants are randomised to either the treatment (0.12% I-C in 0.5% saline spray) or placebo (0.5% saline spray) arm and will prophylactically apply the spray to their nose and throat while completing a daily symptom tracker for a total of 10 weeks. The primary outcome is the acquisition of Covid-19 infection. Secondary outcomes include symptom type, severity and duration, subsequent familial/household Covid-19 infection and infection with non-Covid-19 upper respiratory tract infections. Discussion: Our hypothesis is that I-C sprays will reduce SARS-CoV-2 attachment to the naso- and oropharyngeal mucosal epithelial cells thus reducing the effective viral infective dose. If proven effective, the self-administered prophylactic spray would have wider utility for key workers and the general population. Trial registration number: NCT04590365